Stationary and pulsating vector dissipative solitons in nonlinear multimode interference based fiber lasers - Luo, Yiyang (2022)
Rapid progress in real-time spectroscopy uncovers the spatio-spectral scenarios of ultrashort pulses in dissipative systems. Varieties of transient soliton dynamics on different timescales have been revealed. Here, we report on an experimental observation of stationary and pulsating vector dissipative solitons in a nonlinear multimode interference (NL-MMI) based fiber laser with net normal dispersion. Polarization non-discrimination of the NL-MMI mode-locking facilitates the dissipative soliton trapping process. Two orthogonally polarized components are coupled together through oppositely shifting their central frequencies to form the group-velocity-locked vector dissipative solitons (GVLVDSs). Dispersive Fourier transform (DFT) based polarization resolved measurement enables insights into the transient polarization dynamics and the long-term evolution. Particularly, both stationary and pulsating GVLVDSs are obtained with appropriate parameter settings. It is found that the quasi-stationary pulsating manner is accompanied with recurrent spectral breathing and energy oscillation; the two orthogonally polarized components possess synchronous pulsating manners due to the cross-phase modulation induced trapping mechanism and the similar formation process. Additionally, chaotic pulsation is also captured in sense that the spectra cannot recover to their original profiles despite of the harmonic energy oscillation. All these findings can enhance our understanding towards soliton pulsation with the freedom of vectorial degree.